Entrepreneurship and Its Influencing Factors: The Case of Women Entrepreneurs in Kuwait - Saad, Khadija (Digital Repository of Theses, 2025)
Entrepreneurship, a major economic dynamism aspect that transforms ideas into opportunities is one of the vast facets recognized as critical drivers of a country's economic growth, employment, productivity, and innovation. In Kuwait, a vibrant entrepreneurial ecosystem with women plays a crucial role in its development but the population of women in the business is still significantly lower than their men counterparts. This is attributed by many challenges including social and cultural barriers, lack of self-confidence, economic challenges, and lack of education and support networks. This study aimed to determine factors influencing female entrepreneurs’ effectiveness in Kuwait in the current competitive business arena. Specifically, the study focused on the influ-ence of sociocultural aspects and economic factors in determining the performance of women en-trepreneurs in Kuwait, the role of self-confidence, and women's education in encouraging them to become successful entrepreneurs. The study used a deductive research approach and a quantitative research method. Using conven-ience and snowball sampling technique the study select 100 women entrepreneurs and collected data with the help of well-structured questionnaires. The data was collected through questionnaires and analyzed using descriptive, correlation, and regression analyses. The findings of the study concluded that there are insignificant relationships between socio-cul-tural factors, economic factors, and self-confidence and female entrepreneurs’ effectiveness in the current competitive business arena of Kuwait. The study concluded that education level among women entrepreneurs in Kuwait plays a critical role in encouraging them to become entrepreneurs, but insignificantly influences their performance and growth. Key Words: Entrepreneurs, Effectiveness, Socio-Cultural Factors, Economic Factors, And Self-Confidence